Numerical Analysis of Protection Method of Metallic Sub-Wavelength Concentric Arrays for Radially Polarized Light Selection and Its Applications - Hyuntai Kim (Sensors, 2021)
Radially polarized light has various advantages on sensing, thanks for its symmetric field distribution. To select radial component, metallic sub-wavelength concentric arrays are widely used. To increase the stability of the metallic nanostructure from mechanical or chemical hazards, a method to apply an additional protective layer has been proposed. The structure was numerically calculated, and optimized structure showed ~97.4% of transmittance for radially polarized component with ~20 dB of polarization extinction ratio compared to the azimuthally polarized component. This result is a 22% increase compared to the case without the protective layer. In addition, the utility the protective layer applied to metallic sub-wavelength concentric arrays is also discussed. The structure has been applied to a binary, concentric optical plate, and showed the same function with radially polarized input, but prohibited azimuthally polarized input. The proposed structure is expected to be applied on numerous centrosymmetric flat optical components.